The impact of long-term trends in continuity of care on the medical expenses of hypertensive patients: based on group-based trajectory model - Du, Yanqiu; Liang, Di; Zhang, Gaofeng; Luo, Yongsong; Huang, Jiayan; Dong, Yin (Frontiers in Public Health, 2025)
PurposeThis study aimed to identify long-term trends in continuity of care (COC) among hypertensive patients using group-based trajectory modeling (GBTM) and evaluate their association with medical expenses, thereby providing evidence for chronic disease management.MethodsWe analyzed 6-year (2016–2021) reimbursement data of the social health insurance from Yuhuan City, China, including 30,545 hypertensive adults. Continuity of Care Index (COCI) was calculated annually. GBTM was employed to classify patients into trajectory subgroups based on COCI trends, with the best-fitting model selection guided by Bayesian information criterion (BIC), average posterior probability (AvePP). Multiple linear regression assessed the relationship between trajectory groups and annual medical expenses, adjusting for age, gender, insurance type, and Charlson Comorbidity Index (CCI).ResultsFour COCI trajectories were identified: low-level maintenance (52.06%), low-level increase (17.14%), high-level decrease (18.94%), and high-level maintenance (11.87%). Patients in the high-level maintenance group incurred the lowest annual medical expenses (mean range: ¥3,786–¥5,088), while the low-level maintenance group exhibited the highest (mean range: ¥6,450–¥10,321). After adjustment, the low-level maintenance group had significantly higher expenses than the high-level maintenance group (β = 3,049.44 CNY, p < 0.001). Older age, employee insurance coverage, and higher CCI were also associated with increased medical expenses (p < 0.001).ConclusionSustained high continuity of care correlates with reduced medical expenses in hypertensive patients. Long-term COC maintenance should be prioritized in chronic disease management to mitigate healthcare costs. Policymakers should incentivize care continuity through integrated health systems and targeted patient interventions.